Assessing the Subjective and Physiological Effects of Intranasally Administered Crushed Extended-Release Morphine Formulations with and without a Sequestered Naltrexone Core in Recreational Opioid Users - Beatrice Setnik; Veeraindar Goli; Naama Levy-Cooperman; Catherine Mills; Megan Shram; Ira Smith (Pain Research and Management)
OBJECTIVE: To evaluate the pharmacodynamic (PD) effects of morphine sulfate and naltrexone hydrochloride extended-release (MSN) capsules compared with controlled-release morphine sulfate (MS) and placebo when crushed and administered intranasally.